Pemanfaatan Teknologi Virtual Reality sebagai Media Pengenalan UMKM Jawa Barat Berbasis Aplikasi Artsteps - Putri, Shindi Audina; Voutama, Apriade; Heryana, Nono (Universitas Indraprasta PGRI Jakarta, 2023)
One option for introducing micro, small, and medium enterprises (UMKM) in West Java is through the use of virtual technology, which can potentially visualize different UMKM products interactively. Previously, the introduction of UMKM products relied solely on print media or social media for advertising. Therefore, Virtual Reality technology can be a solution to integrate information about UMKM in West Java. This research utilizes the MDLC (Multimedia Development Life Cycle) method to optimize the design and implementation process of Virtual Reality technology as an integrated information tool with 3D and other media. The end result of this virtual reality utilization research is a virtual tour simulation on